Determination of benzo (a) pyrene in Iraqi Chicken, doner kebab and fish samples cooked with charcoal or gas fire - Jasim, Khalid N.; Shkhaier, Samir L. (Journal of the Faculty of Medicine Baghdad, 2021)
Background: Polycyclic aromatic hydrocarbons (PAHs) have been found in protein-rich food products where they are generated during certain food processing procedures. Benzo[a]pyrene (B(a)P) is a member of a class of PAHs in which the molecular structure includes two or more fused aromatic rings with adjacent rings sharing two or more carbon atoms with the formula C20H12. Dietary intake of these compounds via a formation of B(a)P on processing or cooking lead to metastasis of tumors at several sites, particularly in the upper gastrointestinal tract. Objective: We aimed to determinate B(a)P in charcoal and gas broiled chicken, doner kebab and fish meats taken from some restaurants in Baghdad. Methods: Prospective study was done in Baghdad from july to decemper 2015 in (Palestine st and alsadria). 120 samples of chicken, doner kebab and fish were collected from some resturants in Baghdad area randomly.A 20 cooked samples using a charcoal fire and gas fire for each kind of meat mentioned above to determinate B(a)P in these samples.HPLC technique was used for determination. Results: Mean levels of B(a)P were found to be (11.6±11.08 μg/kg) ,(10.0±9.4 μg/kg) and (8.4±7.8 μg/kg) for a charcoal fire broiled chicken, doner kebab and fish respectively while mean levels of B(a)P were found to be (2.5±1.9 μg/kg) ,(2.3±1.7 μg/kg) and (2.0±1.4 μg/kg) for a gas fire respectively. Conclusion: The B(a)P levels of three samples cooked on a charcoal fire exceeded the maximum tolerance level for B(a)P of the European Union establishment (2005). The highest levels of B(a)P were found in charcoal-grilled samples.Therefore,present study provides important information on B(a)P in charcoal grilled meats in Iraq. This might help to avoid the contamination in food processing to secure food safety and to protect iraqi citizens.